2002
DOI: 10.1097/00006565-200212000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid sequence intubation for pediatric emergency airway management

Abstract: A large, prospective, multicenter observational study of pediatric EDIs was conducted at university-affiliated EDs. RSI is the method of choice for the majority of pediatric emergency intubations; it is associated with a high success rate and a low rate of serious adverse events. Pediatric intubation as practiced in academic EDs, with most initial attempts by emergency and pediatrics residents and fellows under attending physician supervision, is safe and highly successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
3
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(145 citation statements)
references
References 20 publications
5
122
3
15
Order By: Relevance
“…2,[7][8][9][10] In a multi-center observational study Sagarin et al found that of 156 pediatric intubations, 81% were rapid sequence intubations, 13% were without medication and 6% used sedation without neuromuscular blockade. 11 These results are surprising since they are not the same as those found at our service (work in progress at two pediatric ICUs in Porto Alegre, shows a predominance of sedation without neuromuscular blocking agent).…”
Section: Introductioncontrasting
confidence: 53%
“…2,[7][8][9][10] In a multi-center observational study Sagarin et al found that of 156 pediatric intubations, 81% were rapid sequence intubations, 13% were without medication and 6% used sedation without neuromuscular blockade. 11 These results are surprising since they are not the same as those found at our service (work in progress at two pediatric ICUs in Porto Alegre, shows a predominance of sedation without neuromuscular blocking agent).…”
Section: Introductioncontrasting
confidence: 53%
“…[8][9][10] The lowest success rate (67%) was, as expected, in the resident group; however, this rate was similar to the rate of resident success previously described. 11,12 The high success rate (100%) of both PEM and PICU fellows is likely due to the anesthesia rotations that are mandatory and usually completed early in fellowship. The success rate of PEM attending staff (76%) was significantly lower than the published success of emergency medicine attending staff (98%).…”
Section: Discussionmentioning
confidence: 99%
“…69 Use RSI only if you are trained, and have experience using these medications and are proficient in the evaluation and management of the pediatric airway. If you use RSI you must have a secondary plan to manage the airway in the event that you cannot achieve intubation.…”
Section: Ventilation With An Endotracheal Tubementioning
confidence: 99%